214k views
3 votes
Andre solves the following system of equations by elimination. {3a+6b=12 and -3a+6b=-12

2 Answers

1 vote

Answer:

3a+6b=12

-3a+6b=-12

——————-

12b=0

User Insha
by
5.2k points
0 votes
3a + 6b = 12 and
-3a + 6b = -12

if we add the equations, the -3a cancels out leaving:

12b = 0

if we plug it into the first equation, we get 3a + 0 = 12, which simplifies the equation to:

3a = 12

Divide both sides by three and the result is:

a = 4

The final answer is:

a = 4

b = 0

User Daskus
by
6.2k points